2018
DOI: 10.21076/vizyoner.409322
|View full text |Cite
|
Sign up to set email alerts
|

Ön Li̇sans Öğrenci̇leri̇ni̇n Umutsuzluk Algilarinin Çeşi̇tli̇ Deği̇şkenler Açisindan İncelenmesi̇

Abstract: Bu çalışmanın amacı, ön lisans öğrencilerinin umutsuzluk düzeylerini ve umutsuzluk düzeylerinde çeşitli değişkenler açısından (cinsiyet, sınıf düzeyi, anne ve baba öğrenim durumu, gelir durumu, kişilik özellikleri, yaşam kalitesi, sosyal ilişkiler) farklılık olup olmadığının incelemektir. Araştırmanın evrenini Salihli Meslek Yüksekokulu'nda 2017-2018 eğitim öğretim döneminde öğrenim gören öğrenciler oluşturmaktadır. Örneklemi ise araştırmaya gönüllü olarak katılan toplam 272 öğrenci oluşturmaktadır. Araştırmay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…As a result of the study conducted with the students of education faculty, Şahin (2009) concluded that there was no significant difference between the hopelessness scores according to the education level of the mother, but that the father differed significantly according to the education level. Tetik and Yurtsever (2018) found that associate degree students that the The Journal of Limitless Education and Research, 5 (3), 233-260 education level of parents did not differentiate the level of hopelessness. These results are consistent with the results of this study.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 94%
See 2 more Smart Citations
“…As a result of the study conducted with the students of education faculty, Şahin (2009) concluded that there was no significant difference between the hopelessness scores according to the education level of the mother, but that the father differed significantly according to the education level. Tetik and Yurtsever (2018) found that associate degree students that the The Journal of Limitless Education and Research, 5 (3), 233-260 education level of parents did not differentiate the level of hopelessness. These results are consistent with the results of this study.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 94%
“…The fact that people's friendship relationships are good or bad actually does not impact their future perspectives on whether they are hopeful or hopeless. Tetik and Yurtsever (2018) put…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Özellikle 1929 ekonomik krizinin ortaya çıkışı ve sermaye piyasasının çöküşünü izleyen 4 yıl içinde sermaye piyasasının gelişmesinde ve kamunun aydınlatılmasında köklü değişiklik yaratacak düzenlemeler yapılmıştır. (Tetik, Demirel, 2002:1) Kamuyu aydınlatma kavramının özünde, bir durumun açıklanması veya bir durum, olay veya faaliyet hakkında bilgi verilmesi olgusu yatmaktadır. (Eroğlu, 2003:7) Kamuya açıklanan bilgilerde genel olarak aşağıda belirtilen konuların olması gerekmektedir (Kepekçi, 1983:59) 1.…”
Section: Kamuyu Aydınlatmaunclassified
“…Hopelessness is a negative state of emotion that expresses the negative perspective, unwillingness and decreased expectation on the future (Açıkgöz, 2019) and it can cause state of emotions such as helplessness (Tetik & Yurtsever, 2018). In individuals who feel helpless, the feeling of haplessness which is the opinion of being not able to utilize some significant advantages by the impact of bad experiences undergone in the past (Mcmahan, 1996) can arouse as well.…”
Section: Introductionmentioning
confidence: 99%